2014
DOI: 10.5152/akd.2014.4870
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long term continuous positive airway pressure treatment on systolic and diastolic function in patients with obstructive sleep apnoea syndrome: A five year observational study

Abstract: Objective: Evaluation of the long-term effects of continuous positive airway presure (CPAP) on mean heart rate and left ventricular systolic and diastolic parameters in obstructive sleep apnea syndrome (OSAS) using conventional and tissue Doppler techniques. Methods: This prospective cohort study is designed to evaluate the long-term effects of CPAP treatments in normotensive OSAS patients. Initially 40 patients aged from eighteen to fifty five with documented OSAS syndrome were evaluated within one month of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Several studies have shown that the treatment of OSAS with continuous positive airway pressure (CPAP) can reduce pulmonary and/ or hypertensive symptoms [9][10][11][12][13][14][15][16]. In contrast, a significant effect on blood pressure (BP) in treated hypertensive OSAS patients with an apnea-hypopnea index (AHI) of 10 or more events per hour was not described; however, CPAP treatment was used only for 4 weeks [17].…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have shown that the treatment of OSAS with continuous positive airway pressure (CPAP) can reduce pulmonary and/ or hypertensive symptoms [9][10][11][12][13][14][15][16]. In contrast, a significant effect on blood pressure (BP) in treated hypertensive OSAS patients with an apnea-hypopnea index (AHI) of 10 or more events per hour was not described; however, CPAP treatment was used only for 4 weeks [17].…”
Section: Introductionmentioning
confidence: 97%
“…CPAP usage was also associated with reduction in blood pressure 69. CPAP treatment was able to improve left ventricular systolic and diastolic functions as well as reduce mitral regurgitation severity and 24 h mean heart rate after 1 month and 5 years in patients with OSA 70. CPAP treatment in patients with OSA without cardiovascular disease reduced systolic blood pressure, however endothelial functions were not affected 71.…”
Section: Effects Of Treatmentmentioning
confidence: 96%
“…However, the long-term effect of CPAP treatment on cardiac function and structure may be beneficial, but clinical trials, randomized studies including significant number of patients and significant follow up period are scant. In this context, the study of Bilge et al (5) in this issue published in the Anatolian Journal of Cardiology adds to the literature because the authors evaluated the cardiac function of OSA patients after 5-year of CPAP effective treatment. Butt et al (6) found a reduction of the posterior wall thickness, improvement in LV ejection fraction (EF), systolic S velocity, and diastolic LV parameters after a mean of 26 weeks of CPAP treatment.…”
mentioning
confidence: 99%
“…The studies of our group reinforced the improvement in LV and RV function after 6 months of CPAP, especially in those patients with severe OSA who showed higher frequency of LV and RV impairment (3,11). Strengths of Bilge et al (5) study are related to the design: a) prospective cohort study; b) compliance to treatment of at least 5 hours daily; c) long term follow up of 5 years; d) exclusion of uncontrolled high blood pressure. The authors were also careful when reporting LV and RV variables using echocardiography and Doppler techniques.…”
mentioning
confidence: 99%